POLA ASUH ORANGTUA DAN LINGKUNGAN PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA - Harianti, Rini; Amin, Suci (Jurnal Curricula, 2016)
Motivation and learning are two things that affect each other . One of factors that affect the motivation of learning is environment learning and parenting that determine the quality of student learning outcomes. The objective of this study was to examine the correlation between parenting with learning environment and learning motivation of students in cerdas school. The study was conducted in a cerdas school, Tampan Pekanbaru. The sample consists of 57 students in cerdas school. The approach was conducted in this study are qualitative and quantitative. The results showed that positive parenting in terms of parental control (64%), clarity of communication (61%) and the demands of the parents become mature (54%). Students have the internal motivation (68%) and external motivation (55%) in positive learning. There are significant affect and positive among parenting with student learning motivation with significantion value 0.000 and determination coefficient 69.1 percent. It was concluded that parenting affect to learning motivation of students. It is recommended to parents and the school to be able to apply a good parenting style, creating a situation that can stimulate learning interest of students to actively learn and pay attention to the needs of school children.